DISCUSSION OF THE “HOTTEST YEAR ON RECORD” IN AUSTRALIA - Parker, Albert; Ollier, Clifford D. (Quaestiones Geographicae, 2017)
The global temperature trends provided by the Australian Bureau of Meteorology are artificially exaggerated due to subjective and unidirectional adjustments of recorded values. The present paper aims to promote the use of the raw stations’ data corrected only for urban heat island formation. The longer temperature records of Australia exhibit significant oscillations with a strong quasi-60 years’ signature of downward phases 1880 to 1910, 1940 to 1970 and 2000 to present, and upwards phases 1910 to 1940 and 1970 to 2000. A longer oscillation with downward phase until 1910 and an upwards phase afterwards is also detected. The warming since 1910 occurred at a nearly constant rate. Over the full length of the long Australian records since the end of the 1800s, there is no sign of warming or increased occurrence of extreme events. The monthly highest and mean maximum temperatures do not exhibit any positive trend. The differences between monthly highest and lowest, or monthly mean maximum and mean minimum temperatures, are all reducing because of urban heat island formation.